Ease For Buying Medicine Through The Delivery Service at Mazaya Pharmacy - Herman, Gita Angelina; Taryana, Asep (Business Review and Case Studies, 2024)
Background: A pharmacy is a means of pharmaceutical services carried out by pharmacists. Mazaya Pharmacy is one of the pharmaceutical service facilities in the city of Bogor. To date, in-person medication administration is the dominant service provided by pharmacies. However, growing demand for diverse services compels pharmacies to expand their offerings included new alternatives to serve customers, such as home delivery services.Purpose:The results of the analysis are that customers have difficulty buying medicine because they cannot come to the pharmacy directly. or example eElderly customers, young working couples, customers with limited transportation, and customers with certain emergency conditions.hard to come. Methodology/approach: This research aims to analyze the problems faced by customers, using the Design Thinking method approach to find solutions to customer problems. Conclusion: Therefore, this problem can be solved if there is a special service that can solve this customer problem. Mazaya Pharmacy developed a solution in the form of a drug delivery service by utilizing communication facilities via the WhatsApp Business application. The aim of this service is expected to ake it easier for customers to buy medicines by ordering medicines with a delivery service. This delivery service can be an added value in improving the quality of service at the Mazaya Pharmacy which can increase customer satisfaction and loyalty and expand the pharmacy's coverage area..Keywords: customer, delivery service, medicine, pharmacy, pharmaceutical services